Plant analysis diagnostic indices for boron nutrition of mungbean (Vigna radiata L.) cultivars grown in a rainfed calcareous soil. (2nd January 2016) - Rafique, E.; Mahmood-ul-Hassan, M.; Sarwar, S.; Yousra, M.; Ali, I.
ABSTRACT: Boron requirement of mungbean was assessed from yield response curves based on field experiment during 2010-11. Four cultivars, i.e., NM-11, NM-2006, Chakwal Mung-2006 and AZRI Mung-2006 were grown in a boron (B)-deficient calcareous soil by applying B at 0, 0.5, 1.0, 2.0, and 4.0 kg ha −I . Boron application significantly increased grain yield and B uptake by all the mungbean cultivars over control. Maximum grain yield increases were: cv. NM-11, 20%; cv. NM-2006, 24%; cv. Chakwal Mung-2006, 26%; and cv. AZRI Mung-2006, 28%. The cultivars varied in B efficiency and cv. NM-11 was most B efficient (83%) while cv. AZRI Mung-2006 was the least B efficient (78%). Fertilizer B requirement (kg ha −1 ) for 95% of the maximum grain yield was: 0.60 for cv. AZRI Mung-2006, 0.70 for cv. Chakwal Mung-2006, 0.75 for cv. NM-2006, and 0.85 for cv. NM-11. Plant tissue critical B concentration in leaves was higher than in seeds.